Inclusive urbanisation in Tanzania and Uganda - Andersson, Agnes (Lund University, 2025)
The dataset is a household survey covering randomly sampled households in 15 purposively selected small towns in Uganda and Tanzania, surveyed in 2022.

Our survey was designed to explore multiple dimensions of inclusivity and covered
1) household structure and infrastructure; 2) expenditures/assets; 3) rural–urban links
and social networks; 4) socio-economics; 5) work; and 6) voting and participation.
The first three sections pertained to the household and the last to the individual. The
resulting dataset contains 300 variables, with 1,789 respondents in Uganda (seven
towns) and 2,034 in Tanzania (eight towns), totalling 3,823 cases. Our survey is limited
by not tracking change over time, but simply offering a snapshot of years 2021–2022.

The dataset is a household survey covering randomly sampled households in 15 purposively selected small towns in Uganda and Tanzania, surveyed in 2022.

Our survey was designed to explore multiple dimensions of inclusivity and covered
1) household structure and infrastructure; 2) expenditures/assets; 3) rural–urban links
and social networks; 4) socio-economics; 5) work; and 6) voting and participation.
The first three sections pertained to the household and the last to the individual. The
resulting dataset contains 300 variables, with 1,789 respondents in Uganda (seven
towns) and 2,034 in Tanzania (eight towns), totalling 3,823 cases. Our survey is limited
by not tracking change over time, but simply offering a snapshot of years 2021–2022.
Inkluderande urbanisering i små städer i Tanzania och Uganda
Keywords: URBANIZATION; URBANISERING; urban livelihoods; urban försörjning; rural urban linkages; länkar mellan stad-land; political participation; politiskt deltagande; urban agriculture; urbant jordbruk; Human Geography; Kulturgeografi; Economic Geography; Ekonomisk geografi; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap